Nocturnal Hypoxemia Rather Than Obstructive Sleep Apnea Is Associated With Decreased Red Blood Cell Deformability and Enhanced Hemolysis in Patients With Sickle Cell Disease - Stauffer, Emeric; Poutrel, Solène; Cannas, Giovanna; Gauthier, Alexandra; Fort, Romain; Bertrand, Yves; Renoux, Céline; Joly, Philippe; Boisson, Camille; Hot, Arnaud; Peter-Derex, Laure; Pialoux, Vincent; et al. (Frontiers in Physiology, 2021)
Background: Although obstructive sleep apnea (OSA) could act as a modulator of clinical severity in sickle cell disease (SCD), few studies focused on the associations between the two diseases. Research Question: The aims of this study were: 1) to explore the associations between OSA, nocturnal oxyhemoglobin saturation (SpO2) and the history of several acute/chronic complications, 2) to investigate the impact of OSA and nocturnal SpO2 on several biomarkers (hematological, blood rheological and coagulation) in patients with SCD. Study Design and Methods: Forty-three homozygous SCD patients underwent a complete polysomnography recording followed by blood sampling. Results: The proportion of patients suffering from nocturnal hypoxemia did not differ between those with and those without OSA. No association between OSA and clinical severity was found. Nocturnal hypoxemia was associated with a higher proportion of patients with hemolytic complications (glomerulopathy, leg ulcer, priapism or pulmonary hypertension). In addition, nocturnal hypoxemia was accompanied by a decrease in RBC deformability, enhanced hemolysis and more severe anemia. Interpretation: Nocturnal hypoxemia in SCD patients could be responsible for changes in RBC deformability resulting in enhanced hemolysis leading to the development of complications such as leg ulcers, priapism, pulmonary hypertension or glomerulopathy. Clinical Trial Registration: ClinicalTrials.gov, NCT03753854